Project Report on Design and Development of Radar Controller Software on Power PC based Hardware using Linux - YASHASHWINI, SHASHI KIRAN, ADIL PASHA and MANVENDRA (2011)
INTERNAL GUIDE: JISHA P, MVJCE
Keywords: Power PC based Hardware using Linux